2016
DOI: 10.5539/jas.v9n1p164
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Postharvest Quality of “Red Delicious” Apple Fruits Based on Fruit Nutrient Elements Composition

Abstract: Fruit nutrient elements content during harvest could considerably effect on postharvest life of apples. In this study, apple fruits cultivar Red Delicious were harvested at the commercial maturity stage at 20 commercial orchards. Fruits were divided into three groups according to peel color; dark red, medium and light red. The mineral elements nutrient content such as nitrogen, phosphorus, potassium, calcium and magnesium and their ratios were measured in the harvested fruits. Thereafter, fruits were places in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Fertilization strategies affect orchard productivity, fruit size and quality, with fruit quality being highly dependent on nutrition, particularly storage capacity and the development of metabolic disorders [9]. The relationships between certain nutrients, nitrogen, calcium and potassium, and their ratios, apple quality and post-harvest disorders have been founded [7,[10][11][12][13][14][15][16][17]. Implemented and recommended diagnostic methods for the nutritional status of fruit trees are based on leaf analysis at an advanced stage of the cycle 90-110 days after full bloom (DAFB).…”
Section: Introductionmentioning
confidence: 99%
“…Fertilization strategies affect orchard productivity, fruit size and quality, with fruit quality being highly dependent on nutrition, particularly storage capacity and the development of metabolic disorders [9]. The relationships between certain nutrients, nitrogen, calcium and potassium, and their ratios, apple quality and post-harvest disorders have been founded [7,[10][11][12][13][14][15][16][17]. Implemented and recommended diagnostic methods for the nutritional status of fruit trees are based on leaf analysis at an advanced stage of the cycle 90-110 days after full bloom (DAFB).…”
Section: Introductionmentioning
confidence: 99%
“…Several works have shown that a low ratio of Ca/K concentration is related to a high incidence of various disorders such as bitter pit in apple [ 38 ], appearance of water-soaked in peaches [ 39 ], and water-core in pears and apples [ 40 ]. In addition, the Ca/K ratio has been postulated as a good indicator to ensure post-harvest fruit quality [ 41 ]. High concentrations of K can have antagonist effects to Ca in vegetable tissues leading to increased tissue sensitivity to disease and disorder incidence [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, J&K is the leading apple producer and accounts for about 77% of total apple production of the country. Many indigenous apple varieties like Ambri, Kesari, Hazratbali and Maharaji are grown in J&K and studies related to their maturity indices and quality are well documented ( Doryanizadeh et al, 2017 ). From the last few years several exotic varieties have been introduced in J&K to boost the apple industry of India.…”
Section: Introductionmentioning
confidence: 99%